Exploring dimensions of customer satisfaction: An analysis of determinant factors in the experience of consuming AG Food - Ariana, Meta Yoga; Azizah, Nur (Institute of Computer Science (IOCS), 2024)
Increasing competition in the organic food market, including AG Food products, faces challenges from other food brands that are considered healthier. This study aims to analyze the factors that influence customer satisfaction in consuming AG Food products and services. This research was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with a sample of 128 active students at Tanjungpura University. The results showed that service quality and price have a significant influence on user satisfaction. Meanwhile, product quality has no influence on user satisfaction. This research provides insight for AG Food and other culinary businesses to understand the factors that influence customer satisfaction and can improve their business performance in a competitive market.